Understanding the model of user satisfaction in using cloud storage systems of employees in Thailand: A conceptual framework - Najantong, Kulapa; Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok (My University, 2018)
The use of cloud storage technology has been dramatically increased in Thailand especially for most working people. Satisfaction in using cloud storage systems (e.g., for storing and retrieving information) is one of users' criteria for making a decision to use them. The purpose of this study is to develop a model of User Satisfaction of working people in Thailand in order to define relevant factors that affect their use of cloud storage systems. This conceptual framework is based on a technology acceptance theory (TAM3) that considers perceived usefulness and perceived ease of use and on a Unified Theory of Acceptance and Use of Technology (UTAUT2) that considers social influence and user's experience that affect user's satisfaction. In this model, the following service aspects of Cloud storage systems which have been taken from a service satisfaction research are defined as dependent variables: equitable service, timely service, ample service, continuous service and progressive service.
Keywords: cloud storage system; service satisfaction; TAM3; UTAUT2